Urgensi Larangan Penggunaan Senjata Kimia di Suriah menurut The Chemical Weapon Convention 1993 - Ananda, Ar Raffi Ridho; Kusniati, Retno (Uti Possidetis: Journal of International Law, 2022)
This study aims to determine and analyze the application of The Chemical Weapons Convention 1993 "CWC" in the prohibition of the Use of Chemical Weapons and to identify and analyze the protection of victims against the impact of the use of chemical weapons in Syria. The research method used is a normative juridical research type. The results showed that the application of The Chemical Weapons Convention 1993 "CWC" in the prohibition of the use of chemical weapons that Syria's violation of the provisions stipulated by International Humanitarian Law and the settlement made by the OPCW and the United Nations in their cooperation which was resolved only limited to the destruction of weapons. owned by Syria again, no criminal sanctions were found for perpetrators of violations of International Humanitarian Law. Protection of victims against the effects of the use of chemical weapons in Syria is carried out according to the 1949 Geneva Conventions based on Article 27 of Geneva Convention IV 1949, namely: The protected person has the right, in all circumstances, to obtain respect for himself, his dignity, the rights of his family, religious beliefs and worship, and habits and customs. They are treated humanely and protected at all times, in particular against all forms of violence or threats of violence and against public humiliation and curiosity.